2013
DOI: 10.1080/13647830.2012.724180
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the spatio-temporal scales of laminar premixed flames near equilibrium

Abstract: 2013) Analysis of the spatio-temporal scales of laminar premixed flames near equilibrium, Combustion Theory and Modelling, 17:1, 76-108,The interplay between chemistry and transport is addressed by exploring the coupling between the spatial and temporal scales of one-dimensional laminar premixed combustion in reactive mixtures described by detailed chemical kinetics and multicomponent transport. System dynamics are investigated in the neighbourhood of the equilibrium state; in so doing, the time scales associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…For equilibria with positive chemical eigenvalues, λ i,0 > 0, (3.8) identifies critical length scales where the diffusion-modified eigenvalue will be zero, c = mπ Dτ i,0 ; this result is similar to that of Al-Khateeb, Powers, and Paolucci [44]. We note that our boundary conditions and basis functions allow a symmetry in the dynamics in the Galerkin projection of our system.…”
Section: Methodssupporting
confidence: 69%
“…For equilibria with positive chemical eigenvalues, λ i,0 > 0, (3.8) identifies critical length scales where the diffusion-modified eigenvalue will be zero, c = mπ Dτ i,0 ; this result is similar to that of Al-Khateeb, Powers, and Paolucci [44]. We note that our boundary conditions and basis functions allow a symmetry in the dynamics in the Galerkin projection of our system.…”
Section: Methodssupporting
confidence: 69%
“…With the finest length scale of reaction given by Powers & Paolucci (2005) for this mixture finest 10 −4 cm, and the diffusivity of the mixture D mix 10 cm 2 s −1 , one can estimate the frequency of the disturbance for which diffusion clearly dominates as ν D mix / 2 finest = 1 GHz. Useful insights on the relative importance of advection, reaction and diffusion in hydrogen-air chemistry is given by Al-Khateeb et al (2013) in the context of a laminar flame. There, it is shown that diffusion clearly influences the various reaction time scales on length scales given by a classical Maxwellian model, i √ D mix τ i , where i is the reaction length scale associated with the chemical time scale τ i .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was demonstrated by Romick, Aslam & Powers (2012) that for the one-step kinetics model the long time behaviour of the detonation is affected by the addition of viscosity; these viscous effects delay the transition to instability, and in the regime where multiple frequency oscillations exist, viscosity can play a dramatic role. Moreover, Al-Khateeb, Powers & Paolucci (2013) suggested that hydrogen-air mixtures have reaction length scales present which have time scales associated with them over which both chemistry and diffusion can be important. This suggests that viscosity has a role to play in the dynamics of detonations; however, the role of viscosity in pulsating detonations of a detailed kinetics model has not been quantified in a detailed manner.…”
mentioning
confidence: 99%
“…One can calculate a rough estimate of the length scales for these oscillations in a manner similar to that given by Al-Khateeb et al, 20 who estimate the length scale as ℓ = √ D ik τ . For example, the fine diffusion scale diffusion mode is estimated by using the smallest diffusion coefficient, D ik ≈ O(10 1 cm 2 /s), and higher harmonics' time scale and thus yields ℓ ≈ O(10 −4 cm).…”
Section: Hydrogen-air Dynamicsmentioning
confidence: 99%
“…Mazaheri et al 19 demonstrated that diffusion can play an important role in regions of high-resolutions. Furthermore recent calculations done by Al-Khateeb et al, 20 indicate that the fine reaction length scales present in hydrogen-air mixtures can have time scales associated with them at which both chemistry and diffusion become important. Therefore, the introduction of grid-independent physical diffusion should be considered.…”
Section: Introductionmentioning
confidence: 99%